MARKETING RESEARCH IN THE FASHION INDUSTRY - Sabirova, Ziyada Azimjonovna; Jumaniyazova, Ruzakhon Farkhod kizi (INTERNATIONAL CONFERENCES, 2023)
The article provides information on marketing research in the fashion industry, directions and methods of their implementation, as well as the results of marketing research on the study of customers of the Uzbek leather fashion market.